Tick Size, Bid-Ask Spreads, and Market Structure - Huang, Roger D.; Stoll, Hans R. (Journal of Financial and Quantitative Analysis, 2001)
We propose a link between market structure and the resulting market characteristics—tick size, bid-ask spreads, quote clustering, and market depth. We analyze transactions data of stocks traded on the London Stock Exchange, a dealer market. We conclude that market charateristics are endogenous to the market structure. The London dealer market does not have a mandated tick size, and it exhibits higher spreads, higher quote clusterings, and higher market depth than the NYSE auction market. Clustering of trade prices is similar in London and New York.